Legal Protection for Students Participating in Demonstrations: An Analysis of Law Number 9 of 1998 Concerning Freedom of Expressing Opinions in Public - Muhammad Risqi; Mushafi Miftah (CV Edujavare Publishing, 2026)
This study examines legal protection for students in exercising their right to express opinions in public under Law Number 9 of 1998 concerning Freedom of Expressing Opinions in Public, focusing on the reciprocal relationship between Articles 6 and 13 and the challenges of implementation in practice. This study employs a normative juridical method using a statutory approach and a conceptual approach, with the Corrupted Reformation movement presented as an empirical illustration. The findings indicate that Law Number 9 of 1998 establishes a reciprocal legal protection framework through three layers of mechanisms: the definitional and legitimizing layer under Articles 1 and 2; the balancing layer concerning rights and obligations under Articles 5, 6, and 8; and the procedural and sanction-based layer under Articles 9–11 and 15–18. Applying Lawrence M. Friedman's legal effectiveness theory, the study finds that the implementation of such protection continues to face challenges involving the legal substance, legal structure, and legal culture, which mutually reinforce one another. Consequently, normative legal protection cannot be effectively realized without simultaneous improvements across all three dimensions.